PENINGKATAN PARTISIPASI DAN PRESTASI BELAJAR SISWA PADA MATA PELAJARAN IPA DENGAN MODEL DISCOVERY LEARNING KELAS IV SD: PENINGKATAN PARTISIPASI DAN PRESTASI BELAJAR SISWA PADA MATA PELAJARAN IPA DENGAN MODEL DISCOVERY LEARNING - Rossy Fitrianingsih Rossy; Rokayah; Mestika Sekarwinahyu (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2024)
The primary objective of this article is to assess variances in student engagement and academic performance, specifically focusing on the properties of light in the field of natural science. This analysis is conducted by implementing the Discovery Learning model among fourth-grade students at Sukalarang State Elementary School, Manglid State Elementary School, and Gedurahayu State Elementary School in Sukaralang Sub-district, Sukabumi District. Employing a quasi-experimental approach, the research relies on quantitative data analysis. Findings indicate that student participation is highly commendable at Sukalarang State Elementary School, whereas at Manglid State Elementary School and Gedurahayu State Elementary School, participation is deemed satisfactory. Post-treatment, there was a noticeable enhancement in academic achievement, showcasing a significant disparity between pre-treatment and post-treatment results when employing the Discovery Learning model across the three schools. The most substantial improvement in academic achievement was observed at Sukalarang State Elementary School, followed by Manglid State Elementary School, with the smallest increase noted at Gedurahayu State Elementary School. In conclusion, the application of the Discovery Learning method is proven to elevate both student engagement and academic performance in the realm of natural science, particularly concerning the properties of light materials, for fourth-grade students.